PERBANDINGAN PROFIL STRES KERJA PADA DOKTER DI INDONESIA DAN DOKTER MIGRAN ASAL INDONESIA DI JERMAN - Ratri Atmoko Benedictus (Universitas Katolik Indonesia Atma Jaya, 2019)
The high demand for health care workers in Germany creates opportunities for foreigners to work in Germany, including doctors from Indonesia. The difference in cultural context constructs different meanings toward factors of job stress. This study aimed to compare the factors of job stress among doctors in Indonesia and Indonesia's doctors in Germany. KFZA (Kurz-Fragebogen zur Arbeitsanalyse) or Short Questionnaire for Job Analysis is utilized to measure job stress. As many as 12 doctors in Indonesia and 8 Indonesia's doctors in Germany became the participants. As a result, job stress among the two groups triggered by the lack of information and the low opportunity for consultation support. In addition to those factors, job stress among doctors in Indonesia is also triggered by lack of opportunities for comprehensive work, low independence for planning, organizing and decision making, lack of internal social support, poor collaborative work climate, and unsatisfactory organization services.